Moluscos límnicos do semiárido e nordesde brasileiros: conhecimentos atuais, estrutura e dinâmica das comunidades de dois rios intermitentes piauienses - Leal, Manuella Feitosa (2022)
The distribution and abundance of limnic mollusks depend on several abiotic and biotic factors. In the semiarid region, which brings together a diversity of underexplored biological groups, the extreme conditions caused by irregular drought and flood periods lead to the selection of resistant limnic mollusk species, which have adaptive strategies that enable their survival in this region. Despite their important ecological, economic and sanitary role, limnic mollusks are among the most endangered groups and are still poorly studied in the semiarid region. Considering the lack of information about these animals in the Northeast and in the Brazilian semiarid region, mainly for Piauí, the objective of this work was to describe the composition of the mollusk communities of two rivers in that state and to understand which factors contribute to the determination of their structures and dynamics. The mollusks were collected monthly between October/2017 and September/2019, in Itaim River, Itainópolis, and Guaribas River, Picos, Piauí. Environmental variables such as water temperature, depth, type of substrate, presence of aquatic plants, water flow characteristics were obtained through a Rapid Environmental Assessment Protocol. Ordination analyzes were used to test the influence of these environmental variables on the structure and dynamics of communities. Data on the distribution of limnic mollusks in the Northeast and Brazilian semiarid regions were accessed through systematic review and biological collection records. A total of 11 species of the classes Gastropoda and Bivalvia were collected in the rivers, being the first record of Uncancylus concentricus for the Northeast region. For lotic environments in the state of Piauí, Drepanotrema schubarti, Pomacea canaliculata, Pisidium dorbignyi, and Stenophysa marmorata were recorded for the first time. It was possible to establish that the Northeast of Brazil has 71 recorded species, of which 34 occur in the semiarid region. The occurrence of the invasive bivalve Corbicula fluminea in the state of Piauí was also registered, enabling the survey of its current distribution in Brazil in 22 states and in the Federal District, in several ecosystems. The structure and dynamics of mollusk communities in the semiarid region does not have the hydroperiod as the most important factor for its structuring, unlike what was pointed out in other studies. These communities are shaped by a set of factors related to environmental changes of anthropic origin and factors linked to seasonal dynamics, and not just the hydroperiod. PAR was an effective tool to identify these factors, and because it is easily accessible and at no cost, it can be used in studies involving ecology not only of mollusks, but of other limnic organisms. And so, studies carried out on intermittent water bodies in the semiarid region must consider the multiple factors that together shape their limnic communities.